Cause-related marketing: do managers understand and use this tool? - Miranda, Mafalda M. (2020)
Design - We relied on data obtained from in-depth interviews with managers. Data categorization allowed the application of the main constructs of the UTAUT model and the unveiling of the level of acceptance of Cause-Related Marketing (CrM) campaigns by managers and its use as a marketing strategy. Purpose – Most of the research on CrM emphasizes the benefits of these campaigns for charities and donors. The purpose of this study is to decode what managers think about CrM campaigns and try to discern and understand the principal motivations, benefits, and inherent risks to implement these campaigns. Findings - Managers recognize CrM benefits mainly relating them with an increase in reputation and image of the company, making it possible to differentiate and increase its notoriety. However, the social nature of this tool is what weights in the most on the decision of managers, since they recognize that being socially responsible is a competitive factor. The greatest constraints identified have to do with the effort on the implementation of the campaign and with the consumer’s scepticism, especially in transactional campaigns. Originality - With this research we were able to realize that there is a misunderstanding between the CrM concept and purely philanthropic marketing, which can somehow inhibit managers from recognizing the potential of this tool. Regarding CrM use, the position of managers shows a clear concern about the importance of harmonizing values between the company and the cause, betting on long-term campaigns with transparent communication and investing in the process of planning, implementing, and monitoring campaigns to improve their performance. This needs to be taken into account in future assessments of CrM campaigns.